Speckle-tracking echocardiography in the early diagnosis of heart failure after ST-segment elevation myocardial infarction - V. E. Oleinikov; A. V. Golubeva; V. A. Galimskaya; Yu. A. Barmenkova; E. A. Shigotarova; А. V. Babina (Российский кардиологический журнал, 2021)
Aim. To study the potential of global strain analysis using two-dimensional speckletracking echocardiography to predict the heart failure (HF) in patients with ST-segment elevation myocardial infarction (STEMI) based on the 6-month follow-up after revascularization.Material and methods. The study included 114 STEMI patients aged 52 (44; 59) years. Two-dimensional echocardiography was performed with analysis of standard parameters and speckle tracking with analysis of strain and rotational characteristics of the myocardium. Concentration of brain natriuretic peptide was determined. The endpoint was the presence of heart failure (HF) after 6-month follow-up. observation. The analysis of HF risk was carried out using ROC-curves based on 3 criteria. Strain parameters with the maximum sum of sensitivity and specificity were chosen as a cutoff point.Results. Six months after STEMI, depending on the ejection fraction (EF) value, the patients were divided into 3 groups: group 1 — patients with reduced EF (<40%) (HFrEF); group 2 — with mid-range EF (40-49%) (HfmrEF); group 3 — with preserved EF ≥50% (HFpEF). Strain and rotational characteristics differed between groups (p<0,001 for all). It was found that in the acute period of myocardial infarction, global longitudinal strain (GLS) <9,5% (AUR =0,804, 95% (confidence interval (CI) (0,673; 0,936), p=0,001) and global circumferential strain (GCS) <8,7% (AUR =0,722 (95% CI (0,568; 0,875), p=0,012) predicts the development of HFrEF. These values less than 12,5% (AUR =0,830 (95% CI (0,749; 0,911), p=0,001) and 13% (AUR =0,759 (95% CI (0,664; 0,855), p=0,001) is associated with HFmrEF The Twist had the highest predictive value in relation to HFrEF — 4,2° (AUR =0,998 (95% CI (0,993; 0,100), p=0,001).Conclusion. GLS, GCS and Twist have high sensitivity and specificity and can be used in wide clinical practice as simple and cost-effective indicators of HF risk.